The Law of Treasure-Trove: How it can be best adapted to accomplish useful results (Proceedings of the Society of Antiquaries of Scotland, 1862)
This article covers the arguments and conclusions of Alexander Henry Rhind's paper on the difficulties caused by contemporary treasure trove laws. He ends the paper by recommending that Scotland adopt a system closer to that of Denmark. The Society established a committee to present these suggestions to the relevant authorities.